Production improvement in ACM manufacturing company using lean manufacturing approach - Sidek, Kamsidi @ Abd Malek (2013)
ACM Sdn. Bhd. is a manufacturing company, in which to continuously commit on improvement process which based on the fundamental goal, to minimize or eliminate waste while maximizing production flow. The purpose of this study is to develop a value stream mapping for a ACM Sdn. Bhd. and it was begin with creating a current state map and understand the production flow and the current cycle times. This provides the information needed to produce a future state map. The goal is to identify and eliminate the waste, which is any activity that does not add value to the final product, in the production process. In order to collect the information needed, the study was conducted within the production facility to enable the researcher gained knowledge and familiarized with the production flow and the activities being performed at the shop floor. Parameters such as cycle times, down times, work in process (WIP) for inventory and material, and information flow paths were recorded. This information will enable the researcher to visualize the current state of the process activities by mapping the material and information flow and looking for opportunities to eliminate wastes. ARENA simulation software package was used to simulate and analyze the process flow and times. Result from the analysis shows that there are areas where the ACM Sdn. Bhd. can further improve their production system. Improvements in cycle times of 13-22% are possible by new arrangement of the layout. The results can be used as a guide to the ACM for improvement and implement the lean manufacturing concept in their manufacturing system.